Deskripsi Perilaku Kecemasan Komunikasi Mahasiswa Bimbingan dan Konseling Universitas Pendidikan Indonesia - Hasna Nurul Sani; Euis Farida; Eka Sakti Yudha (Universitas Mathla'ul Anwar Banten, 2021)
COMMUNICATION APPREHENSION TENDENCY ON STUDENTS GUIDANCE AND COUNSELING AT INDONESIA UNIVERSITY OF EDUCATION. Adequate competence in communicating without experiencing communication apprehension is very needful for the student to be able to communicate effectively, and achieve success in academic or career in the future. Communication apprehension would affect negatively in life. This study aims to determine the description of communication apprehension tendency of student guidance and counseling at the Indonesia University of Education. Respondent in this study is student guidance and counseling 2nd grade at the Indonesia University of Education in aggregate 33 students. The data collection process is through instruments with the Personal Report of Communication Apprehension (PRCA-24). The approach used is quantitative with descriptive research methods. The results of the study describe the percentage of achievement scores of students’ communication apprehension tendencies in the moderate category is amount to 23 students, 2) students guidance and counseling experience high communication apprehension in the interpersonal conversation context.